PERANAN NOTARIS DALAM PENDAFTARAN JAMINAN FIDUSIA DI KOTA SAWAHLUNTO - Abd. Rahmad, Jeri Rizal dan (Normative Jurnal Ilmiah Hukum, 2021)
Notary not only acts as a fiduciary guarantee deed maker, the notary is also responsible for online access that is carried out, including if there is an error in accessing data, it is the full responsibility of the Notary. The general obstacles faced include: Lack of thoroughness of notary staff in inputting fiduciary guarantee data online, causing the notary to have to make improvements to the access and be subject to PNBP again, the network to access AHU services is often disrupted considering the geographical conditions of Sawahlunto City and many parties access through the site and the signal strength of the internet provider used by a notary to access online AHU services, Sometimes there are difficulties in paying PNBP for fiduciary registration through Yapp. To overcome these obstacles, this can be done by: Adding or assisting other notary staff, if the file fiduciaries who enter in large numbers, Looking for a good quality internet provider, and carrying out access not during peak hours, such as morning and evening, Problems using this Yapp must contact the BNI office that issued the Yapp card.